Reverberation of the use value: Daily life, corporeity, and enjoyment in the Baroque Ethos - Smart, Ángeles (2020)
Use value, body and enjoyment make up a possible conceptual universe from which to tackle the baroqueethos. A generous regime in the use of objects and natural and cultural resources is at its base: in theornament, clothing, decorations, in the use of words, in the government of gestures or in the practices ofthe kitchen. Like art, baroque behavior is prodigal, splendid, garigoleado. This work reviews those aspectsof Bolívar Echeverría’s reflection that underline in the baroque ethos his strategy that affirms the bodilyand material dimension of the use value. Strategy that reverberates and expands towards ways of lifeand organization, where eros, ecstasy and abundance acquire prominence and primacy.